Long-term NMDA receptor inhibition affects NMDA receptor expression and alters glutamatergic activity in developing rat hippocampal neurons. (3rd July 2015) - Sinner, Barbara; Friedrich, Oliver; Lindner, Regina; Bundscherer, Anika; Graf, Bernhard M.
Abstract: Ketamine and its stereoisomer S(+)-ketamine are widely used for sedation in pediatric anesthesia and intensive care medicine. Numerous experimental studies indicate that ketamine is potentially toxic to the developing brain. Here, we examined the long-term effects of NMDA receptor blockade on NMDA receptor subunit expression, alterations in neuronal Ca 2+ -oscillations and apoptosis. Hippocampal neurons, 15 days in culture, were exposed to either S(+)-ketamine or the NMDA receptor blocker MK801 for 24 h. Cytosolic Ca 2+ -concentration was determined by fluorescence microscopy and the expression of the NMDA subunits NR1, NR2A and 2B was assessed by qRT-PCR, whereas Western blots and activated Caspase-3 served to measure the extent of apoptosis. Long-term incubation with MK801 or higher doses of S(+)-ketamine resulted in a dose-dependent decreased ability of MK801 to reduce amplitude and frequency of the Ca 2+ -oscillations 15 min following washout of the drug. This was accompanied by an increase in NR1 mRNA but not the NR2A and B subunit expression at the same time point. 24 h following washout of the specific drug, a significant elevation of the pro-apoptotic marker BAX, as well as activated Caspase-3 positive neurons, could be detected in cultures exposed to 100 μM MK801 and 25 μM S(+)-ketamine. Here, we show that long-term blockade of the NMDA receptor in developing rat hippocampal neurons significantly increased NR1 subunit expression, and that this was associated with an alteration in neuronal activity. Apoptosis was only induced 24 h after withdrawal of long-term blockade for high doses of S(+)-ketamine.